Monitoring Suspended Sediment Dynamics Using MBES - Simmons, Stephen M. (2010)
This technical note describes use of a multibeam echosounder (MBES) to quantify the dynamics of suspended sediment in a large open channel. A methodology is detailed that uses the backscatter magnitude from the MBES water-column data to adjust the magnitude of sonar returns for the various sonar settings, spatially and temporally average the data to account for the random nature of acoustic backscatter from the suspended sediment, and calibrate the processed data with direct samples. A case study of flow at the confluence of the Rio Paraná and Rio Paraguay, Argentina, where there is a distinct turbidity difference along the mixing interface of the two flows, is used to demonstrate the unique capabilities of MBES to quantify sediment concentrations and dynamics within the water column.